A Quantum Cascade Laser-Based Optical Sensor for Continuous Monitoring of Environmental Methane in Dunkirk (France) - Maamary, Rabih (Sensors (Basel), 2016)
A room-temperature continuous-wave (CW) quantum cascade laser (QCL)-based methane (CH(4)) sensor operating in the mid-infrared near 8 μm was developed for continuous measurement of CH(4) concentrations in ambient air. The well-isolated absorption line (7F(2,4) ← 8F(1,2)) of the ν(4) fundamental band of CH(4) located at 1255.0004 cm(−1) was used for optical measurement of CH(4) concentration by direct absorption in a White-type multipass cell with an effective path-length of 175 m. A 1σ (SNR = 1) detection limit of 33.3 ppb in 218 s was achieved with a measurement precision of 1.13%. The developed sensor was deployed in a campaign of measurements of time series CH(4) concentration on a site near a suburban traffic road in Dunkirk (France) from 9 to 22 January 2013. An episode of high CH(4) concentration of up to ~3 ppm has been observed and analyzed with the help of meteorological parameters combined with back trajectory calculation using the Hybrid Single Particle Lagrangian Integrated Trajectory (HYSPLIT) model of NOAA.